1977
DOI: 10.1073/pnas.74.12.5721
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ovarian “inhibin”: Suppression of the secondary rise in serum follicle stimulating hormone levels in proestrous rats by injection of porcine follicular fluid

Abstract: Margoliash, September 20, 1977 ABSTRACT The present studies were carried out to see if porcine follicular fluid could inhibit increases in serum follicle stimulating hormone (FSH) levels when injected into the rat. For these studies the pentobarbital-treated proestrous rat was chosen as the major test animal model. If an artificial surge of luteinizing hormone (LH) is administered to these rats, it can induce a synchronized secondary rise in FSH secretion rate. Normal saline-treated rats were also used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(62 citation statements)
references
References 20 publications
3
58
0
1
Order By: Relevance
“…Activins and inhibins were first identified as important regulators of pituitary follicle-stimulating hormone release. (14)(15)(16)(17) Subsequent studies have demonstrated that activins are expressed in diverse tissues and play important roles in embryology, wound healing, and tissue homeostasis. (18)(19)(20)(21)(22) Activins signal by binding either the activin receptor type IIA (ActRIIA) or the activin receptor type IIB, which recruits the type I receptor, activin-like kinase 4 (Alk4), leading to phosphorylation of cytoplasmic Smads 2/3.…”
Section: J Jbmrmentioning
confidence: 99%
“…Activins and inhibins were first identified as important regulators of pituitary follicle-stimulating hormone release. (14)(15)(16)(17) Subsequent studies have demonstrated that activins are expressed in diverse tissues and play important roles in embryology, wound healing, and tissue homeostasis. (18)(19)(20)(21)(22) Activins signal by binding either the activin receptor type IIA (ActRIIA) or the activin receptor type IIB, which recruits the type I receptor, activin-like kinase 4 (Alk4), leading to phosphorylation of cytoplasmic Smads 2/3.…”
Section: J Jbmrmentioning
confidence: 99%
“…This hypothesis is supported by an inverse relationship between plasma concentrations of inhibin and FSH during the periovulatory period (Kimura et al 1983, Hasegawa et al 1989, Watanabe et al 1990, Woodruff et al 1996. In addition, administration of an inhibin preparation or recombinant human inhibin A in the rat abolishes the rise of FSH during oestrus (Schwartz & Channing 1977, Rivier & Vale 1991. In contrast, the blockade of GnRH does not eradicate the secondary surge of FSH in the rat.…”
Section: Figurementioning
confidence: 50%
“…Porcine follicular fluid also contains a factor that specifically inhibits the secretion of FSH from the pituitary gland (Schwartz & Channing, 1977;Welschen, Hermans, Dullaart & de Jong, 1977). This factor is produced by granulosa cells (Erickson & Hsueh, 1978;Hermans, van Leeuwen, Debets, Sander & de Jong, 1982), and has an action which is identical to that of inhibin in the male (de Jong & Sharpe, 1976).…”
Section: Introductionmentioning
confidence: 99%